1985
DOI: 10.1111/j.1365-2125.1985.tb05141.x
|View full text |Cite
|
Sign up to set email alerts
|

The metabolism and pharmacokinetics of nicardipine hydrochloride in man.

Abstract: 1 Studies have been carried out to investigate the disposition of nicardipine hydrochloride following intravenous and oral administration to male volunteers. 2 Following oral administration of a radiolabelled dose, nicardipine was shown to be rapidly and extensively metabolised and to be rapidly eliminated from plasma. 3 After intravenous infusion of nicardipine at 5 mg-' for 3 h, plasma levels declined biexponentially, and clearance values were of the same order as hepatic blood flow. 4 With repeated oral a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

1987
1987
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(35 citation statements)
references
References 5 publications
0
35
0
Order By: Relevance
“…The overall correlation between the pharmacokinetic parameters, such as AUC, and the level of renal function suggests that the reduction in plasma clearance of nicardipine is related either directly to the deterioration in renal function (which is unlikely) or indirectly to the effects of renal dysfunction on hepatic metabolism. After oral administration nicardipine is subject to extensive hepatic metabolism (Higuchi et al, 1977;Rush et al, 1986) which may be saturable at relatively low concentrations (Graham et al, 1985;Seki & Takenaka, 1977). Thus the clearance of nicardipine ultimately depends on both liver blood flow and hepatocellular function.…”
Section: Discussionmentioning
confidence: 99%
“…The overall correlation between the pharmacokinetic parameters, such as AUC, and the level of renal function suggests that the reduction in plasma clearance of nicardipine is related either directly to the deterioration in renal function (which is unlikely) or indirectly to the effects of renal dysfunction on hepatic metabolism. After oral administration nicardipine is subject to extensive hepatic metabolism (Higuchi et al, 1977;Rush et al, 1986) which may be saturable at relatively low concentrations (Graham et al, 1985;Seki & Takenaka, 1977). Thus the clearance of nicardipine ultimately depends on both liver blood flow and hepatocellular function.…”
Section: Discussionmentioning
confidence: 99%
“…profiles for the nicardipine study is shown in Figure 1. (Bourbigot et al, 1986 (Graham et al, 1985; peak concentration 0.4-0.5 FM), concentrations in the hepatocytes may well be much higher than those measured in plasma. Diltiazem has been demonstrated to have a protective effect on posttransplant tubular necrosis in renal transplant patients despite significantly higher CsA whole blood concentrations (Wagner et al, 1988).…”
Section: Resultsmentioning
confidence: 82%
“…Nicardipine has also been used experimentally as a probe to study the effects of calcium channel antagonists on the role of sympathetic nervous system activity in the development of cardiovascular risk (Van Swieten et al, 1997). The pharmacokinetic parameters of nicardipine are non-linear due to hepatic first-pass metabolism, thus, the extent of oral bioavailability (F) was low about 35% following a 30 mg dose at steady state (Graham et al, 1984;Graham et al, 1985). It is a substrate of cytochrome P450 (CYP) 3A subfamily, especially CYP3A4 in humans and forms to pharmacologically inactive metabolite (Higuchi and Shiobara, 1980;Guengerich et al, 1986;Guengerich, 1991).…”
Section: Introductionmentioning
confidence: 99%